Book Review: Experimental Archaeology Presented in the AiD Magazine - Roeland P Paardekooper (EXARC Journal, 2012)
The top popular magazine in Germany on archaeology is called Archäologie in Deutschland, simply referred to as ‘AiD’. It has been published every two months since 1984 and is 84 pages in length. The publisher is Theiss from Stuttgart. They publish on archaeology, history and ethnography and carry about 650 titles. AiD carries many adverts for their publications, as well as offers from others.